2008
DOI: 10.4028/www.scientific.net/amm.13-14.85
|View full text |Cite
|
Sign up to set email alerts
|

Local Effects during Indentation of Fully Supported Sandwich Panels with Micro Lattice Cores

Abstract: Abstract. This paper discusses the penetration behavior of fully supported sandwich panels with micro-lattice and foam cores, and composite skins. This behaviour is of importance during foreign object impact and perforation of sandwich structures. Experimental results are given for quasi-static penetration of micro-lattice and foam blocks, and it is shown that these two cellular materials are comparable. Experimental results are also given for drop weight penetration of fully supported skinned panels, and it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In this section, a theoretical approach for predicting the plastic collapse strength à pl for the BCC micro-lattice block is introduced. Collapse of different micro-lattice structures will entail different mechanisms as elastic buckling, plastic buckling, axial plasticity, bending plasticity, rupture, etc [11].…”
Section: Prediction Of the Plastic Collapse Strength ã Plmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, a theoretical approach for predicting the plastic collapse strength à pl for the BCC micro-lattice block is introduced. Collapse of different micro-lattice structures will entail different mechanisms as elastic buckling, plastic buckling, axial plasticity, bending plasticity, rupture, etc [11].…”
Section: Prediction Of the Plastic Collapse Strength ã Plmentioning
confidence: 99%
“…Recently, at the University of Liverpool, the rapid prototyping manufacturing process of selective laser melting (SLM) has been used to realize lattice structures at the microscale [11]. Figure 1(a) shows a typical micro-lattice block (termed a body centred cubic, BCC).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced manufacturing techniques such as the rapid prototyping selective laser melting (SLM) technique [7] has strongly contributed to the initial study on the metallic micro-lattice structure at the University of Liverpool. Work has been carried out in studying the mechanical properties, crush behaviours, as well as impact properties of the SLM SS316L stainless steel and Ti64 titanium alloy micro-lattice [6][7][8][9][10]. However, it should be noted that the mechanical properties of the SLM micro-lattice structures are very much influenced by two processing parameters that are laser power (in Watt [W]) and laser exposure time (in micro seconds [µs]) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it has been shown that the level of impactor penetration for a given impact energy is similar for fully supported and simply supported panels. 24 Figure 13(a) shows typical load versus displacement traces for the SS316L and ALPORAS sandwich panels. The lattice cores were manufactured using two sets of parameters, these being 70 W × 1000 µs and 140 Watts × 1000 µs.…”
Section: Resultsmentioning
confidence: 99%